Impact of a Media Campaign on Consumers’ Purchasing Intentions of Legal Timber in Cameroon - Belinga, B.; Chervier, C.; Lescuyer, G. (Informa UK Limited, 2021)
Illegal logging is a key driver of deforestation in tropical countries and benefits a large number of stakeholders, including urban domestic buyers. Changing the latter’s purchasing behavior could produce significant shifts in the illegal trade market. Based on survey data (n= 463), this paper assesses the impact of a media campaign on consumers’ purchase intentions for legal timber and wooden furniture in Yaoundé and analyses the underlying psychological mechanisms. Combining covariate matching and mediation analysis, we found a significant positive effect of the media campaign on the declared intention to purchase legally-sourced timber and the mediation effect of two out of three precursors of the theory of planned behaviors, namely attitude and subjective norms. This study provides critical inputs to frame future media campaign messages and, by demonstrating some consumers’ interest in legal timber, to strengthen the domestic legitimacy of policies such as the Forest Law Enforcement, Governance and Trade.